Who is left standing when the tide retreats? Negotiating hospital discharge and pathways of care for homeless people. Issue 3 (21st December 2015) - Whiteford, Martin; Simpson, Glenn
Abstract : Purpose: – The critical potential of hospital discharge policies and practices to ameliorate the health and social care needs of homeless people has become the focus of considerable interest in England. Central to this rise in policy formation and practice development is an acute understanding of the multiple exclusions homeless people face in navigating public health and social care systems. In ways small and large this nascent landscape is serving to redefine and reshape hospital arrangements for homeless people, and opening-up new ways to deliver care across clinical, social and therapeutic boundaries. The purpose of this paper is to seek to add empirical vigour and theoretical rigour to this unfolding policy and practice terrain. Design/methodology/approach: – This paper draws on findings from a case study concerned with exploring and explaining how statutory and voluntary sector organisations use specialist hospital discharge policies and practices to coordinate pathways of care for homeless people. Findings: – This paper illustrates how people affected by homelessness and ill-health are routinely denied access to statutory housing support, social work assessments and district nursing provision through acts of institutional gatekeeping and professional abrogation. Originality/value: – This paper makes an important contribution to understandings of the connections between hospital discharge arrangements for homeless people and statutory housing, social work and district nursing provision.